Impact of Consumer Sentiment on Defensive and Aggressive Stock Returns: Indian Evidence - Yelamanchili, Rama Krishna (International Journal of Economics and Financial Issues, 2019)
This paper aims to study predictive ability of consumer sentiment of individual stocks. We consider two proxies for sentiment. One is explicit (Index of Consumer Sentiment, ICS), second is implicit (Broad Market Indicator, S&PBSE500) and we pick 50 stocks randomly from S&PBSE500 index. We collect monthly data of all the variables. We group stocks into defensive and aggressive based on their beta value. We posit that sentiment indicators have contemporaneous co-movements and significant predictive ability of defensive and aggressive stocks. Results show contemporaneous co-movement exists between implicit sentiment indicator and stocks; contrarily no such relation exists between explicit sentiment indicator and stocks. We find causation from ICS to S&PBSE500. Both the sentiment indicators have causal relation with aggressive stocks but not with defensive stocks. Result show that only ICS has short-term predictive power of aggressive stocks. We find significant negative relation between consumer sentiment and aggressive stock returns in the following month. This implies high consumer optimism in current month results in price shrink of aggressive stocks in following month. We conclude that implicit sentiment indicator has no predictive ability of stocks and explicit sentiment indicator is able to predict only small number of aggressive stocks. We suggest investors not to follow sentiment indicators blindly because these indicators predictive ability is very limited that too with select aggressive stocks. We find aggressive stocks have high volatility and gain investor attention during optimistic and pessimistic market conditions. Keywords: Retail investor, investor sentiment, stock returns, noise trade, predictive analytics, JEL Classifications: G40, G41, G14, G17 DOI: https://doi.org/10.32479/ijefi.8368